Гарри Поттер и философский камень: роман / Дж. Роллинг - Ролинг Джоан Кэтлин (Чтение, 2003)
Экземпляры: БС (20170906) / Инвентарный номер: РТШ49840 / Сис.шифр: И(Англ) / Авт.знак: Р 79 / ГРНТИ: 17.82.93 / ББК: 84(4/8)